Analisis Implementasi Kebijakan Penanganan Tindak Pidana Pencucian Uang pada KPK - Haliem Suharso; Vishnu Juwono (Mahesa Research Center, 2022)
This article to get an overview of the implementation of the policy on the handling of the Crime of Money Laundering, as an important enforcement policy for asset recovery, which is focused on the Deputi Penindakan the KPK for the 2016-2019 period, in order to approach this problem, the Normalization Process Theory approach will be used (May & Finch, 2009). Through qualitative research methods, data is collected through interviews with relevant sources, both policy makers, KPK leaders and structural enforcement officers, as well as the main policy implementing officers, namely Investigators and Asset Tracking Officers as well as looking at secondary data such as the KPK Strategic Plan, Annual Report, Accountability Report, investigation warrant and other KPK internal documents. This study of policy implementation through the Normalization Process Theory Approach concludes that in the policy for handling money laundering offenses at the KPK for the 2016-2019 period, policy makers have understood the urgency of handling money laundering offenses (coherence), policy implementers are consciously involved in the policy (cognitive participation), and mutual trust in policy implementation (collective action) but with a note that there is no special forum for monitoring the policy (reflexive monitoring).